2014
DOI: 10.1017/s0007114514003110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oligofructose supplementation on body weight in overweight and obese children: a randomised, double-blind, placebo-controlled trial

Abstract: Limited evidence suggests that the dietary inclusion of oligofructose, an inulin-type fructan with prebiotic properties, may increase satiety and, thus, reduce energy intake and body weight in overweight and obese adults. The aim of the present study was to assess the effect of oligofructose supplementation for 12 weeks on the BMI of overweight and obese children. A total of ninety-seven children aged 7-18 years who were overweight and obese (BMI . 85th percentile) were randomly assigned to receive placebo (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 32 publications
3
56
0
1
Order By: Relevance
“…Furthermore, they maintained their BMI Z‐score, whereas those in the placebo group had significant increases in BMI Z‐score after 12 months . In contrast, a clinical trial by Liber and Szajewska showed that 8 g/d of OFS consumption in otherwise‐healthy overweight or obese children 7–11 years old and 15 g/d in those 12–18 years old did not result in improvements in BMI Z‐score after 12 weeks compared with placebo control. There were also no improvements in the secondary outcomes of change in body weight and difference in absolute body fat or in other metabolic outcomes.…”
Section: Targets For Prebiotics: Gut Microbiota and Adipose Tissue‐rementioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, they maintained their BMI Z‐score, whereas those in the placebo group had significant increases in BMI Z‐score after 12 months . In contrast, a clinical trial by Liber and Szajewska showed that 8 g/d of OFS consumption in otherwise‐healthy overweight or obese children 7–11 years old and 15 g/d in those 12–18 years old did not result in improvements in BMI Z‐score after 12 weeks compared with placebo control. There were also no improvements in the secondary outcomes of change in body weight and difference in absolute body fat or in other metabolic outcomes.…”
Section: Targets For Prebiotics: Gut Microbiota and Adipose Tissue‐rementioning
confidence: 92%
“…Tanner developmental staging was assessed by Abrams et al , and all subjects were a Tanner stage 2 or 3. In contrast, Liber and Szajewska did not include Tanner staging. Because subjects were between 7 and 18 years old, pubertal stage varied considerably within the study which could also account for differences.…”
Section: Targets For Prebiotics: Gut Microbiota and Adipose Tissue‐rementioning
confidence: 99%
“…In select cases, these treatments have been associated with smaller increases in BMI and fat mass (32), and reductions in body weight z-scores, body fat, and trunk fat (33). Still, other prebiotic trials in overweight children have reported no significant beneficial effects (34).…”
Section: Introductionmentioning
confidence: 99%
“…Interpreting the mixed outcomes of prior prebiotic clinical trials in pediatric obesity though is complicated by several challenges. First, in vivo studies in pediatric obesity to date have each used only one prebiotic supplement due to the logistical constraints of clinical trials (3234). Trials employing testing only a single type of supplement hinder the ability to generalize conclusions regarding the efficacy of prebiotics and also make it challenging to determine whether some prebiotics are inherently more acidogenic than others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation